A Modern Method to Monitor Office Blood Pressure - Emiliya Khazan; Augustus Hough (University of Minnesota Libraries Publishing, 2017)
The diagnosis and management of hypertension relies on accurate and precise blood pressure (BP) measurements and monitoring techniques. Variability in traditional office based BP readings can contribute to misclassification and potential misdiagnosis of hypertension, leading to inappropriate treatment and possibly avoidable adverse drug events. Both home blood pressure monitoring (HBPM) and 24-hour ambulatory blood pressure monitoring (ABPM) can improve characterization of BP status over traditional office values and can predict cardiovascular morbidity and mortality risk; however, they are limited by availability and/or practical use in many situations. Available in-office blood pressure measuring methods include manual auscultation, automated oscillometric, and automated office blood pressure (AOBP) devices. A strong correlation exists between AOBP and awake ABPM measurements and has been linked to better prediction of end-organ damage and white coat response compared to standard office BP methods. While AOBP does not provide nocturnal BP readings, it can be utilized in several outpatient settings, and has the capability to decrease utilization of ABPM, white coat effect, and improve optimization of cardiovascular assessment, evaluation, and therapeutic assessment in clinical practice. Hypertension affects over 80 million adults in the United States (US) and is a major risk factor for cardiovascular morbidity and mortality [1]. The condition's ubiquitous nature and broad impact potentially makes understanding the diagnosis and treatment of hypertension key elements of managing cardiovascular risk. Though much attention is paid to the treatment of hypertension, from 2009 to 2012, 45.9% of US patients with hypertension were uncontrolled [1]. Appreciating the aspects of proper assessment of blood pressure is crucial and creates the foundation for approaching hypertension management. Until recently, hypertension was defined as an appropriately measured office systolic blood pressure (SBP) of greater than or equal to 140 mmHg and/or diastolic blood pressure (DBP) greater than or equal to 90 mmHg, with the patient seated and resting for 5 minutes in a proper position, and preferentially, measured as an average of two readings taken 1 or 2 minutes apart [1-5]. While serving as the primary method, standard office blood pressure assessment with either manual or traditional automated BP cuffs is limited in accuracy and application in everyday practice, and faces many challenges. As such, an understanding of the potential limitations of current BP strategies, and the roles and rationale for novel assessment techniques are of value to clinicians [6]. Conflict of Interest: We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Review